Radclyffe Hall: A life in the writing - Dellamora, Richard (University of Pennsylvania Press, 2011)
The Well of Loneliness is probably the most famous lesbian novel ever written, and certainly the most widely read. It contains no explicit sex scenes, yet in 1928, the year in which the novel was published, it was deemed obscene in a British court of law for its defense of sexual inversion and was forbidden for sale or import into England. Its author, Radclyffe Hall, was already well-known as a writer and West End celebrity, but the fame and notoriety of that one book has all but eclipsed a literary output of some half-dozen other novels and several volumes of poetry. In Radclyffe Hall: A Life in the Writing Richard Dellamora offers the first full look at the entire range of Hall's published and unpublished works of fiction, poetry, and autobiography and reads through them to demonstrate how she continually played with the details of her own life to help fashion her own identity as well as to bring into existence a public lesbian culture. Along the way, Dellamora revises many of the truisms about Hall that had their origins in the memoirs of her long-term partner, Una Troubridge, and that have found an afterlife in the writings of Hall's biographers. In detailing Hall's explorations of the self, Dellamora is the first seriously to consider their contexts in Freudian psychoanalysis as understood in England in the 1920s. As important, he uncovers Hall's involvement with other modes of speculative psychology, including Spiritualism, Theosophy, and an eclectic brand of Christian and Buddhist mysticism. Dellamora's Hall is a woman of complex accommodations, able to reconcile her marriage to Troubridge with her passionate affairs with other women, and her experimental approach to gender and sexuality with her conservative politics and Catholicism. She is, above all, a thinker continually inventive about the connections between selfhood and desire, a figure who has much to contribute to our own efforts to understand transgendered and transsexual existence today.
Keywords: 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; discipline; europe; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; royaume-uni; régions géographiques; thématiques; études littéraires

Femmes de la rive gauche - Benstock, Shari (Des femmes, 1987)
Femmes de la Rive gauche étudie les contributions à la vie du Paris littéraire entre 1900 et 1940 de grandes Américaines et Anglaises, telles que Djuna Barnes, Natalie Barney, Sylvia Beach, Caresse Crosby, Nancy Cunard, Hilda Doolittle, Janet Flanner, Anaïs Nin, Jean Rhys, Gertrude Stein, Edith Wharton… Écrivain.e.s, éditeurices, libraires, journalistes, tenant salon au cœur du Paris culturel, elles ont nourri de leur énergie créatrice originale le grand mouvement de la modernité. Cet essai, qui considère à la fois l’histoire littéraire et la littérature, écrit la face cachée du tissu culturel, explore la richesse d’une écriture que le modernisme a tenté de nier…. « Au lieu d’intersection de la vie et de l’art, au croisement de la mémoire et de l’histoire, à la confluence du mythe et de la biographie… j’ai retrouvé les traces de celles qui ont nourri de leur force et de leur intelligence le grand mouvement culturel moderniste. » S. B.
http://catalogue.bnf.fr/ark:/12148/cb349656237
Keywords: 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; arts; cours; discipline; europe; france; his4860; histoire de l'art; histoire des femmes*; histoire et politique; littérature française; modernité; paris; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires